Effect of stone powder and practical evaluation on mechanical property of manufactured sand concrete - Suhang Yang; Zhifeng Xu (Journal of Asian Architecture and Building Engineering, 2025)
Manufactured sand concrete (MSC) is a specific type of concrete successfully employed in many projects and structures made of reinforced concrete, and improving concrete structures. The important characteristic of mechanical sand is that the fine aggregate contains stone powder composed of particles which could pass 75 urn BS sieve. The influence of different stone powder contents on the properties of hardened concrete was studied through experiments. In addition, the experimental relations for estimating the mechanical parameters of MSC compared with CC is presented in this paper. Specimens made of MSC were prepared, on which the axial compression test, cube compression test, splitting test, flexural test and elastic modulus test were conducted. The experimental relations were obtained between the compressive strength, tensile strength and elastic modulus for MSC, and their validity were then investigated. Stone powder can fill the pores in the MSC, improve the overall grading of mechanism sand concrete, improve its working performance, and help to improve the mechanical strength of MSC. The optimum value of stone powder content is accepted as 7.5–10%. The conclusions obtained can provide a basis for the research and promotion application of mechanism sand concrete. The results indicated that the obtained relations could be used to estimate the mechanical properties of MSC with accuracy.